2025 ATMI National Convention (Spokane, WA) (Journal of the Association for Technology in Music Instruction, 2025)
This file lists the papers, compositions, performance/papers, workshops, and demonstrations presented at the 2025 ATMI National Convention, in Spokane, WA October 30 - November 1, 2025.
Keywords: Table of Contents; program